Village infrastructure monitoring system in the web-based community development and empowerment program (P3md) - Luana Lestari Sirait; Suendri; Imam Adlin Sinaga (Institute of Computer Science (IOCS), 2023)
Riah Naposo Village is a village located in Simalungun Regency, North Sumatra. In Indonesia, Riah Naposo Village also took part in the Village Community Empowerment Development Program (P3MD) during its rampant period. In practice, data processing and information are still conventional. Therefore, Riah Naposo Village was unable to distribute and execute development projects efficiently. Besides reducing work efficiency, conventional data processing can also lead to misinformation in recording, fraud in project management, and rampant corruption. By utilizing a web-based application, which aims to create a monitoring system that can monitors, and records all activities carried out related to P3MD in Riah Naposo Village.